Migration as development strategy? The new political economy of dispossession and inequality in the Americas - Phillips, Nicola (Review of international political economy : RIPE, 2009)
In the context of a severe contraction of 'development space' for Latin American and Caribbean economies in the global political economy, we are witnessing a novel and increasingly explicit articulation of migration as a national development strategy by governments in the region. This is particularly pronounced in the Caribbean basin (defined to include Mexico). In response to the shifting shape of the transnational division of labor, the core development strategy that is being articulated is one of insertion into transnational supply chains on the basis of the provision of labor, in the sense both of populating the new transnational professional workforce and of ensuring a continual supply of cheap, low- or unskilled, often undocumented workers to a huge range of sectors in cities and outside them. This article contends that what is thereby put in place is a new political economy of inequality in the Americas, through which a dominant, transnationalized form of 'accumulation by dispossession' can be reinforced and deepened. This transnationalized form of accumulation by dispossession combines, in highly contingent ways, with the distinctively 'nationalized' governance of migration to constitute a contemporary political economy of migration in the Americas in which the developmental potential of labor mobility is subject to profound constraints.